Basal thumb arthritis. Issue 975 (31st January 2007) - Dias, Richard; Chandrasenan, Jeevan; Rajaratnam, Vaikunthan; Burke, Frank D
Abstract : Basal thumb arthritis is a common condition seen in hand clinics across the United Kingdom and is often associated with other pathological conditions such as carpal tunnel syndrome and scaphotrapezial arthritis. Typically, patients complain of pain localised to the base of the thumb. This pain is often activity related, particularly after excessive use involving forceful pinch. A detailed history and examination is normally all that is needed to make the diagnosis. Provocative manoeuvres may be helpful in localising symptoms to the basal joint with degenerative changes or synovitis. Radiographs are useful for confirming the diagnosis and staging the disease in order to plan for surgery. The mainstay of initial treatment of basal thumb arthritis of any stage is activity modifications, rest, nonsteroidal anti-inflammatory drugs, exercises and splinting. A variety of surgical procedures are available to treat the condition when conservative measures have failed, in order to control symptoms and improve function. We review the current literature and discuss the clinical aspects of this condition, staging, and treatment options available, and the difficulties treating this group of patients.